Development of Video Media Basic Techniques of Petanque Game - I Gede Suwiwa; I Ketut Budaya Astra; I Wayan Muliarta; Hendra Mashuri (Universitas PGRI Palembang, 2022)
The purpose of this study was to develop a video learning media product for the basic techniques of the petanque game. This type of research is development research by applying five steps, namely 1) analysis, 2) design, 3) development, 4) implementation, 5) evaluation. The number of respondents who reviewed teaching materials was 3 experts, 49 students. The instruments used to obtain data about the quality of teaching materials are questionnaires and tests. Performance tests are used to determine student learning outcomes between before and after using learning video media teaching materials during the field test. Product validation results by content experts with a total percentage of 90.00% with very good qualifications. The results of product validation by learning media experts with a total percentage of 90.00% with very good qualifications. The results of product validation by learning design experts with a total percentage of 93.30% with very good qualifications. The results of student research on the feasibility of the developed video media showed a percentage of 92, 62% which was the average of the individual test, small group test, and large group test where these results showed a very good category. Field results show that the video media developed has a significant influence on student learning outcomes and higher effectiveness. The results of the paired sample t-test from the pre-test and post-test showed sig (2-tailed) .000 which was smaller than the standard probability of .005 while the N-Gain results showed 6 students were in the medium category and 24 students indicated the high category. This study shows that the video media teaching materials have met the feasibility aspects of content, media, design and are suitable for use by students.